2019
DOI: 10.1080/21691401.2019.1687506
|View full text |Cite|
|
Sign up to set email alerts
|

Ras-PI3K pathway promotes osteosarcoma progression via regulating VRK1-mediated H2A phosphorylation at threonine 120

Abstract: Background: Ras-PI3K pathway aberrant activation plays an important role in the occurrence and development of osteosarcoma. This study investigated the functions of Ras-PI3K pathway specific activation on histone H2A phosphorylation at threonine 120 (H2A T120ph) in osteosarcoma cells, along with the possible internal molecular mechanisms. Methods: Cell transfection was done to alter Ras G12V/Y40C , H2A T120ph and vaccinia-related kinase 1 (VRK1) expression. Then, cell viability, proliferation, migration and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…H, C et al [27]. clari ed that the MAPK pathway played a crucial role in the invasion and metastasis of bladder cancer cells.S, C et al [28]have found that the upregulation of myosin light chain kinase (MYLK) and activation of cGMP-PKG signaling pathway can silence serine / arginine repeat matrix protein 2-selective splicing (SRRM2-AS), thus inhibiting nasopharyngeal carcinoma cell proliferation, colony formation, angiogenesis, blocking the cell cycle and enhancing apoptosis.Studies by Xu, X, et al [29] found that the Pi3K pathway was speci cally activated, vaccine-associated kinase 1 was up-regulateed (VRK1), and then histone H2A was induced to be up-regulated, eventually promoting the progression of osteosarcoma. S, J, et al [30]clari ed that the signaling pathway of transforming growth factor-β (TGF-β) was involved in many cellular processes in mature organisms and developing embryos.…”
Section: Discussionmentioning
confidence: 99%
“…H, C et al [27]. clari ed that the MAPK pathway played a crucial role in the invasion and metastasis of bladder cancer cells.S, C et al [28]have found that the upregulation of myosin light chain kinase (MYLK) and activation of cGMP-PKG signaling pathway can silence serine / arginine repeat matrix protein 2-selective splicing (SRRM2-AS), thus inhibiting nasopharyngeal carcinoma cell proliferation, colony formation, angiogenesis, blocking the cell cycle and enhancing apoptosis.Studies by Xu, X, et al [29] found that the Pi3K pathway was speci cally activated, vaccine-associated kinase 1 was up-regulateed (VRK1), and then histone H2A was induced to be up-regulated, eventually promoting the progression of osteosarcoma. S, J, et al [30]clari ed that the signaling pathway of transforming growth factor-β (TGF-β) was involved in many cellular processes in mature organisms and developing embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is frequently hyperactivated in OS and contributes to increased proliferation and invasion, inhibition of apoptosis, angiogenesis, and chemoresistance [ 91 , 92 ]. Moreover, activation of this pathway has been associated with lung metastasis and poorer prognosis [ 93 ].…”
Section: Nf-κb Dysregulation and Cancermentioning
confidence: 99%